LEGAL UNITS UNDER THE ORAL LANGUAGES IN KARAKALPAK FOLK FRIENDS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the study of elements of the Oghuz language used in Karakalpak folk epics. It identifies the reasons for the use of elements of the Oguz language in the language of epics.